2014
DOI: 10.1097/sle.0b013e3182a50e3a
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Track Versus Standard Care in Laparoscopic High Anterior Resection

Abstract: The value of fast-track (FT) multimodal recovery programs in improving hospitalization of surgical patients has been widely proved. The application of FT protocols to laparoscopic colorectal surgery seems to maximize the effects of the minimally invasive approach. The objectives of this randomized-controlled trial are to compare the short-term outcomes (bowel function, return to oral nutrition, day of discharge, fatigue, time to resume normal activities, functional capabilities, and readmission rate) of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 3 publications
0
34
0
5
Order By: Relevance
“…This article aimed to review the literature in comparing patient satisfaction and QOL following treatment with an enhanced recovery protocol after colorectal surgery to that following standard postoperative care. The 15,18,23 albeit with small differences in outcome that disappear over time. The cause of higher pain scores in the early postoperative period in these select studies remains unclear, and could possibly be related to more enforced early mobilization, lack of routine use of regional or epidural pain management, or decreased administration of oral or intravenous opioid pain relief in favor of nonopioid multimodal therapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This article aimed to review the literature in comparing patient satisfaction and QOL following treatment with an enhanced recovery protocol after colorectal surgery to that following standard postoperative care. The 15,18,23 albeit with small differences in outcome that disappear over time. The cause of higher pain scores in the early postoperative period in these select studies remains unclear, and could possibly be related to more enforced early mobilization, lack of routine use of regional or epidural pain management, or decreased administration of oral or intravenous opioid pain relief in favor of nonopioid multimodal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported no difference. 16,[19][20][21] Jakobsen et al 22 and Mari et al 23 reported faster return to activities within the ERAS group. Only Delaney et al 15 reported worse emotional and mental health scores at discharge in the ERAS group as measured by the SF-36 instrument, which is likely attributed to earlier time of discharge (shorter length of stay) in the ERAS group.…”
Section: Quality Of Life and Return To Activitiesmentioning
confidence: 95%
See 3 more Smart Citations